2014
DOI: 10.1016/j.ijantimicag.2014.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a collection of Streptococcus pneumoniae isolates from patients suffering from acute exacerbations of chronic bronchitis: In vitro susceptibility to antibiotics and biofilm formation in relation to antibiotic efflux and serotypes/serogroups

Abstract: a b s t r a c tThe correlation between Streptococcus pneumoniae serotypes, biofilm production, antibiotic susceptibility and drug efflux in isolates from patients suffering from acute exacerbations of chronic bronchitis (AECB) remains largely unexplored. Using 101 isolates collected from AECB patients for whom partial (n = 51) or full (n = 50) medical details were available, we determined serotypes (ST)/serogroups (SG) (Quellung reaction), antibiotic susceptibility patterns [MIC (microdilution) using EUCAST an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In this regard, the serotypes we tested might differ for biofilm amount and architecture under different experimental settings, as observed previously by Allegrucci et al (2006) using a continuous-flow biofilm reactor system. Similarly to Vandevelde et al (2014), no significant correlation was also seen between biofilm amount and susceptibility to antibiotics among the isolates investigated. Further studies focusing on these topics are needed to understand better the role of biofilm formation in pneumococcal pathogenicity.…”
Section: Discussionmentioning
confidence: 80%
“…In this regard, the serotypes we tested might differ for biofilm amount and architecture under different experimental settings, as observed previously by Allegrucci et al (2006) using a continuous-flow biofilm reactor system. Similarly to Vandevelde et al (2014), no significant correlation was also seen between biofilm amount and susceptibility to antibiotics among the isolates investigated. Further studies focusing on these topics are needed to understand better the role of biofilm formation in pneumococcal pathogenicity.…”
Section: Discussionmentioning
confidence: 80%
“…Biofilm formation is a critical aspect from the pathogenesis perspective because S. pneumoniae has been reported to form biofilms in the upper respiratory tract (Wu et al, 2017;Iverson et al, 2019;Silva and Sillankorva, 2019) and nasopharyngeal colonization is the initial step in this process and the prerequisite for developing IPD (Bogaert et al, 2004). Interestingly, active infection is also associated to pneumococcal biofilms in meningitis by binding to brain microvascular endothelial cells and in persistent respiratory infection affecting patients with cystic fibrosis or chronic obstructive pulmonary disease (COPD) (Orihuela et al, 2009;Vidal et al, 2013;Vandevelde et al, 2014;Dennis et al, 2018). In the biofilm state, pneumococcal cells express the PspC protein in a higher extent, and this protein is the bacterial ligand associated to the recruitment of factor H and therefore to the cleavage of the C3 complement system protein deposited on the bacterial surface (Domenech et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The observed reduction of biomass was even lower, ranging from 50% on young biofilms to 20% or less on old biofilms [45]. In follow-up work, the same group, working on a large strain collection, found that there was no correlation between biofilm formation and intrinsic susceptibility or expression of resistance determinants in pneumococci [46]. Interestingly, this work compiled a table with the activities of the antibiotics on biofilms at concentrations found in epithelial lining fluid with the specific aim of providing indications for the clinical relevance of the pharmacodynamic data obtained [45].…”
Section: Resistance To and In Biofilmsmentioning
confidence: 98%